Peran Badan Permusyawaratan Desa Dalam Menampung Dan Menyalurkan Aspirasi Masyarakat Desa Jang Kecamatan Moro Kabupaten Karimun - Aunur Rafiq; Muhamad Asrizal (UIR Press, 2020)
Village Consultative Agency is a government order that serves as discussing and agreeing on the Draft Village Regulation with the Village Head, Accommodating and channeling the aspirations of the village community, and supervising the performance of the Village Head. Bpd's commitment to the village government certainly gives great hope to the villagers for the realization of a clean, strong and good village government. The presence of BPD can at least provide a balance of power at the level of village government. The purpose of this research is to find out and analyze how the implementation of the role of the Village Consultative Agency Jang Moro District Karimun Regency, and to know and analyze what obstacles faced in displaying the Role of the Village Consultative Agency Jang Moro District Karimun in responding to the aspirations of the community. In this study the authors used qualitative research types and used descriptive methods. Descriptive method is research that tries to give the best possible picture of an individual, circumstance, or group. The results of research on the role of BPD in the implementation of accommodating and channeling the aspirations of the villagers jang district Moro Karimun district from the answers of informants related to social structures in its implementation has not followed the existing rules in the Regulation of the Minister of Home Affairs No. 110 of 2016 on village consultative bodies have not been carried out properly, and in this case the role of BPD can not be felt by the community. This can be seen from the results of the interview above as a whole the role of BPD in accommodating and channeling the aspirations of the community has not had a good impact on development in Teluk Jang Village. Such as the lack of road access development that has been delivered by the community.